Le coton, sa culture et son utilisation selon les sources arabes médiévales - Jean-Charles Ducène (Revue d'ethnoécologie)
Technical literature of the Arab medieval sources indicates a slow but continuous progression of cotton from the Iranian region towards the West, with significant regional variations. Most of the terms used to describe the plant and its products are borrowed from Pahlavi and integrated very early in the Arabic language, which indicates the long history of the adoption of the fibre. From the 10th century onwards, botanical and agronomic works record the spread of the product towards the West and the singularisation of the professions linked to cotton, whether for the treatment of the fibre or the sale of the product.